An early experiment with "permazero" - Stephen F. Quinn; William Roberds (Federal Reserve Bank of Atlanta, 2017)
We investigate a monetary regime with persistent, near-zero policy interest rates ("permazero" in the terminology of Bullard 2015). This regime was implemented in 1683 by a prominent early central bank called the Bank of Amsterdam ("Bank"). The Bank fixed its policy rate at one-half percent and held it unchanged for more than a century. Maintaining the rate helped stabilize the value of Bank money. We employ archival data to reconstruct the Bank's activities during a portion of that interval (1736-91) for which data are most readily available. The data suggest that "permazero" worked well for long periods because the Bank counteracted market swings with quantitative operations. These same data show how fiscal exploitation denied the Bank sufficient resources to stabilize large shocks, with adverse results.
Keywords: E58; E65; N13; 330; central banks; monetary policy; zero lower bound